Integrated system technology of POME treatment for biohydrogen and biomethane production in Malaysia - Zainal, Bidattul Syirat; Ahmad, Mohd Azwan; Danaee, Mahmoud; Jamadon, Nashrah Hani; Mohd, Nuruol Syuhadaa; Ibrahim, Shaliza (MDPI, 2020)
In recent years, production of biohydrogen and biomethane (or a mixture of these; biohythane) from organic wastes using two-stage bioreactor have been implemented by developing countries such as Germany, USA and the United Kingdom using the anaerobic digestion (AD) process. In Thailand, biohythane production in a two-stage process has been widely studied. However, in Malaysia, treating organic and agricultural wastes using an integrated system of dark fermentation (DF) coupled with anaerobic digestion (AD) is scarce. For instance, in most oil palm mills, palm oil mill effluent (POME) is treated using a conventional open-ponding system or closed-digester tank for biogas capture. This paper reviewed relevant literature studies on treating POME and other organic wastes using integrated bioreactor implementing DF and/or AD process for biohydrogen and/or biomethane production. Although the number of papers that have been published in this area is increasing, a further review is needed to reveal current technology used and its benefits, especially in Malaysia, since Malaysia is the second-largest oil palm producer in the world.